Frontispiece: Natural Products Originated from the Oxidative Coupling of Tyrosine and Tryptophan: Biosynthesis and Bioinspired Synthesis. Issue 8 (5th February 2021) - Tang, Shanyu; Vincent, Guillaume
Abstract : Oxidative coupling between tyrosine and tryptophan residues of peptides allows living organisms to produce highly intricate natural products. Their respective biosynthesis inspired synthetic chemists to develop innovative strategies to access these structurally challenging compounds. For more details see the Minireview by G. Vincent and S. Tang on page 2612 .